PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN BUDAYA ORGANISASI TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Ruri M Frista Sibuea (2022)
This research is a quantitative study that aims to determine the effect of managerial ownership, institutional ownership, and organizational culture on the disclosure of Corporate Social Responsibility with the audit committee as a moderating variable. This study uses gender diversity as a measurement for organizational culture variables. The object of this research is mining and manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2018 2021, with a total sample of 113 data. The technique for analyzing the data in this study uses a regression model selection test, classical assumption test, multiple linear regression test, and regression test). hypothesis using STATA software version 16 and a significance level of 5% (0.05). The results of the test show that (1) managerial ownership has a negative effect on the disclosure of Corporate Social Responsibility, (2) institutional ownership has a positive effect on the disclosure of Corporate Social Responsibility, (3) gender diversity does not affect the disclosure of Corporate Social Responsibility, (4) the audit committee cannot moderate the effect of managerial ownership on the disclosure of Corporate Social Responsibility, (5) the audit committee cannot moderate the effect of institutional ownership on the disclosure of Corporate Social Responsibility, and (6) the audit committee can moderate the effect of gender diversity on the disclosure of Corporate Social Responsibility.